The Dynamics of the Elements of Abuse of Authority in the Authority of the Administrative Court After the Enactment of the Latest Job Creation Law - Utama, Alif Wili (Faculty of Law, Universitas Pekalongan, 2024)
Abuse of authority as part of testing the discretionary authority of the State Administrative Court has changed with the presence of Law No. 6 of 2023 concerning Job Creation. Changes can be seen in Article 175 number 2 of the UUCK which expands discretion by eliminating the requirement that it is contrary to the law. However, Law No. 30 of 2014 also does not emphasize the definition of authority testing, thus creating problems, namely the blurring of the parameters of discretion testing by the State Administrative Court Judges. The author also conducts a comparative study with France to find trends in global solutions in solving problems. This research uses normative legal research methods that analyze applicable laws and regulations accompanied by literature studies in the form of books, journals, and other literature. The dynamics of the elements of Abuse of Authority from the UUAP to the birth of the existence of the UUCK has brought the consequences of a paradigmatic shift in the concept of discretion, which was originally limited to be freed because of the elimination of the requirement not to conflict with the provisions of the legislation. However, considering that discretion is actually only the (free) authority possessed by a State Administrative Officer to make a decision and/or take an action, the decision and/or action as a manifestation of the discretionary authority is still bound by the provisions of Article 52 of the UUAP regarding the legal requirements of a decision. The State Administrative Justice System in France and Indonesia has a difference that lies in the phrase used, in France using the term abuse of power, or what is called detournement de pouvoir. This reason is used if an official in issuing an administrative decision deliberately uses his/her authority for purposes that deviate from the original purpose/intention, in contrast to Indonesia which defines abuse of authority more complexly as a form of exceeding authority, mixing authority, and arbitrariness.